The Effect of the Peer-Review Technique on Students’ Writing Ability - Martin Kustati; Yuhardi Yuhardi (Universitas Syiah Kuala, 2014)
The aim of this study was to investigate if there could be a significant positive effect by using Peer-Review Technique (PRT) on students‟ ability in writing English. An experimental research method was used in this study. A writing test based on the indicators of Jacobs et al. (1981) was completed by 65 undergraduate students in English from the English Department at the Faculty of Education and Teacher Training in the State Institute for Islamic Studies “Imam Bonjol‟ at Padang. The students were divided into two groups: an experimental group (n=33) and a control group (n=32). Both groups were similar in terms of academic level, the given writing task and their target language [English] proficiency. The experimental participants were introduced to Peer-Review Technique in essay writing sessions whilst the control group participants were taught through the teacher’s traditional feedback (TTF) whereby students worked individually to produce their texts. The findings showed that PRT gave a significant improvement effect on the students‟ writing abilities. This study is expected to serve as (1) data for further developing PRT; (2) input for lecturers in writing to develop more effective and innovative learning; and (3) additional material for the development of critical and cooperative learning theories in teaching writing.